Hygienic Foundations of the Educational Process in Preschool Institutions - Kurbanova Hurliman Amangeldievna; Shopurova Gulibona (Scholars Digest Publishing, 2023)
In recent years, against the background of negative trends in the dynamics of children's health, there has been a significant increase in mental and physical stress. Preschool institutions focus on maximum satisfaction of the needs of parents in the education of children, in the introduction of additional educational services in the preschool environment, which is not always built taking into account the age and individual characteristics of children. This leads to an excessive load on the child's body, which in turn can lead to a psych emotional breakdown, inability and unwillingness to perceive the material, loss of motivation to learn and even to various health disorders. The latter is confirmed by data on a 3.5-fold increase in the number of children with neuropsychiatric health disorders among preschool children at the age stage from 5-7 years of life.
Keywords: daily routine, preschoolers, educational regime, classes, junior and middle groups.